Female infertility: Traditional methods of treatment and IVF in patients with endocrine disorders - E. B. Rudakova; T. V. Strizhova; E. A. Fedorova; L. Yu. Zamakhovskaya (Лечащий Врач)
An obstetrician-gynecologist of the women’s clinic to whom a married couple with complaints about the absence of pregnancy addresses for the first time, must clearly know the basic algorithm of the examination, medical tactics, and conservative methods of treatment in patients with endocrine disorders. The primary care specialist must also know the indications for surgical treatment and send the patient to the surgical hospital in a timely manner. When conducting examinations and traditional treatment of the detected pathology together with an endocrinologist, the obstetrician-gynecologist should always think and remember the terms of traditional treatment, in order not to miss the «Golden period» for in vitro fertilization.